Genome-Wide Profiling of DNA Methylome and Transcriptome Reveals Epigenetic Regulation of Potato Response to DON Stress - Shi, Yan; Qin, Yuan; Li, Fenglan; Wang, Haifeng (Frontiers in Plant Science, 2022)
Potato is an important food crop that occupies lesser area but has greater production than rice and wheat. However, potato production is affected by numerous biotic and abiotic stresses, among which Fusarium dry rot is a disease that has significant effect on potato production, storage, and processing. However, the role of DNA methylation in regulating potato response to Fusarium toxin deoxynivalenol (DON) stress is still not fully understood. In this study, we performed DNA methylome and transcriptome analyses of potato tubers treated with five concentrations of DON. The global DNA methylation levels in potato tubers treated with different concentrations of DON showed significant changes relative to those in the control. In particular, the 20 ng/mL treatment showed the largest decrease in all three contexts of methylation levels, especially CHH contexts in transposon regions. The differentially methylated region (DMR)-associated differentially expressed genes (DEGs) were significantly enriched in resistance-related metabolic pathways, indicating that DNA methylation plays an essential role in potato response to DON stress. Furthermore, we examined lesions on potato tubers infested with Fusarium after treatment. Furthermore, the potato tubers treated with 5 ng/mL and 35 ng/mL DON had lesions of significantly smaller diameters than those of the control, indicating that DON stress may induce resistance. We speculate that this may be related to epigenetic memory created after DNA methylation changes. The detailed DNA methylome and transcriptome profiles suggest that DNA methylation plays a vital role in potato disease resistance and has great potential for enhancing potato dry rot resistance.